1983
DOI: 10.1007/bf01805813
|View full text |Cite
|
Sign up to set email alerts
|

Paired comparisons between early treated PKU children and their matched sibling controls on intelligence and school achievement test results at eight years of age

Abstract: Early-treated PKU children were compared to their matched non-PKU sibling controls on Wechsler Intelligence Scale for Children (WISC) and Wide Range Achievement Test (WRAT) results at age 8. Fifty-five PKU children had mean WISC Full Scale IQ score of 100, in comparison to a mean of 107 for their matched sibling controls (p = 0.001). Treatment parameters significantly correlated with sibling-PKU IQ score differences included maximum diagnostic phe level (r = 0.244, p = 0.036) and phe levels at age 6 (r = 0.329… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 4 publications
2
32
0
3
Order By: Relevance
“…They also score slightly lower than their unaffected parents or siblings. 26,27 Cognitive outcomes are significantly correlated inversely to blood Phe levels. During a critical developmental period (age 0 -12 years), each 100 mol/L rise in Phe levels predicted a 1.3-to 3.1-point decline in IQ scores among children treated early with dietary therapy.…”
Section: Cognitive and Psychiatric Symptoms Of Pku Cognitivementioning
confidence: 98%
“…They also score slightly lower than their unaffected parents or siblings. 26,27 Cognitive outcomes are significantly correlated inversely to blood Phe levels. During a critical developmental period (age 0 -12 years), each 100 mol/L rise in Phe levels predicted a 1.3-to 3.1-point decline in IQ scores among children treated early with dietary therapy.…”
Section: Cognitive and Psychiatric Symptoms Of Pku Cognitivementioning
confidence: 98%
“…Early treatment of phenylketonuria (PKU) is highly effective in preserving general intellectual abilities [6,11,19] but many authors have reported neuropsychological/cognitive dysfunction [5,8,9,12,[14][15][16]20]. Little is known about effects of treatment on personality development 9 Aspects of family functioning and emotional development secondary to treatment may add to the problems [2].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that, with treatment initiated early, children with PKU attain IQ scores within the normal range, although the scores are often lower than those of non-FKU siblings or parents (Berry, Bofinger, O'Grady, & Perlmutter, 1979;Koch, A;:en, Friedman, & Williamson, 1984;Smith, Beasley, & Ades, 1990). Despite the obvious beneficial effects of a low phe diet, children with PKU have been found to have specific behavioral and cognitive deficits not accounted for by the slightly lower level of intelligence.…”
mentioning
confidence: 95%